2016
DOI: 10.1093/bfgp/elw014
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation and hypertension: emerging evidence and challenges

Abstract: Hypertension is a multifactorial disease influenced by an interaction of environmental and genetic factors. The exact molecular mechanism of hypertension remains unknown. Aberrant DNA methylation is the most well-defined epigenetic modification that regulates gene transcription. However, studies on the association between DNA methylation and hypertension are still in their infancy. This review summarizes the latest evidence and challenges regarding the role of DNA methylation on hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 97 publications
1
24
0
5
Order By: Relevance
“…Lower levels of DNA methylation has been implicated in the development of atherosclerosis and hypertension . The association of lower diastolic blood pressure with LINE‐1 methylation found here and by Han et al is in keeping with our study. Pearce et al observed an association between LINE‐1 DNA methylation and fasting concentrations of glucose, triglycerides and total cholesterol, LDL and HDL cholesterol and also HDL:LDL ratio considered to be an increased risk biomarkers for cardiovascular diseases and Type 2 diabetes .…”
Section: So What Does It Mean?supporting
confidence: 93%
See 2 more Smart Citations
“…Lower levels of DNA methylation has been implicated in the development of atherosclerosis and hypertension . The association of lower diastolic blood pressure with LINE‐1 methylation found here and by Han et al is in keeping with our study. Pearce et al observed an association between LINE‐1 DNA methylation and fasting concentrations of glucose, triglycerides and total cholesterol, LDL and HDL cholesterol and also HDL:LDL ratio considered to be an increased risk biomarkers for cardiovascular diseases and Type 2 diabetes .…”
Section: So What Does It Mean?supporting
confidence: 93%
“…Pearce et al observed an association between LINE‐1 DNA methylation and fasting concentrations of glucose, triglycerides and total cholesterol, LDL and HDL cholesterol and also HDL:LDL ratio considered to be an increased risk biomarkers for cardiovascular diseases and Type 2 diabetes . Nevertheless, some other authors propose the role of epigenetics modification as a biomarker of CVD, independently of established risk factors . The association between the degree of LINE‐1 methylation status and decrease in cholesterol/HDL cholesterol ratio over time suggests a complex interaction between DNA methylation and the other factors, principally statin prescription.…”
Section: So What Does It Mean?mentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible therefore that intrinsic differences in the relative activity of 11‐βHSD2, 11‐βHSD1, and the cortisol reductases contribute to the variation in metabolism seen in these patients. Such differences may be caused by genetic differences affecting expression or activity, such as the polymorphisms in 11‐βHSD2 that associate with hypertension, 34 or epigenetic variation, as studies in rats and in humans have shown differential methylation of the 11‐βHSD2 locus is associated with hypertension 35–37 . Whilst the examples given affect 11‐βHSD2 activity, genetic and epigenetic variation at other loci may also contribute to differences in cortisol metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, 5-methylcytosine (5mC) DNA methylation is a stable and inheritable epigenetic modification. Aberrant 5mC DNA methylation is the most well-defined epigenetic modification that regulates gene transcription affecting the pathogenesis, duration, and severity of essential hypertension [10,11]. For example, decreased global 5mC level in peripheral blood is correlated with increased essential hypertension severity [11,12].…”
Section: Introductionmentioning
confidence: 99%